Sarcopenia in the Setting of Nonalcoholic Fatty Liver - Cabello-Verrugio, C (OAE Publishing Inc., 2022)
Nonalcoholic fatty liver is a worldwide common problem with more prevalence in non-Asian populations that is closely correlated with the muscle-related disorder sarcopenia. The incidence of both health issues has been observed to be strongly interlinked where presence of one exacerbates the other. Nonalcoholic fatty liver disease (NAFLD) pathophysiology increases the muscle loss, while the onset of NAFLD in sarcopenic patients aggravates the liver problems as compared to non-sarcopenic patients. Scarcity of research on the subject provides very little evidence about the cause and effect of disorders. No FDA approved drugs are available to date for NAFLD and sarcopenia. Research is underway to understand the complex biochemical pathways involved in the development of both disorders. This review is a small contribution toward understanding sarcopenia in the setting of NAFLD that provides insight on the common pathophysiological profile of sarcopenia and NAFLD and portrays a novel way of delving into the subject by introducing the concept of cortisol crosstalk with the muscle-liver axis. Sarcopenia and NAFLD are considered metabolism-related problems, and cortisol, being a glucocorticoid, plays an important role in metabolism of fats, carbohydrates, and proteins. Cushing’s syndrome, characterized by abnormally elevated concentrations of blood cortisol/enhanced intracellular activity, shares many pathologic conditions (such as insulin resistance, metabolic syndrome, abnormal levels of specific cytokines, and obesity) with NAFLD and sarcopenia. Hence, cortisol can be a potential biomarker in sarcopenia and NAFLD. As cortisol activity at cellular level is controlled by 11β-hydroxysteroid dehydrogenase type 1 and 2 (11β-HSD1/2) enzymes that convert inactive steroid precursor into active cortisol, these enzymes can be targeted for the study of sarcopenia and NAFLD. Combined studies on NAFLD and sarcopenia with respect to cortisol open a new avenue of research in the understanding of both disorders. © The Author(s) 2022.